A "double-locked" probe for the detection of hydrogen sulfide in a viscous system. Issue 54 (11th June 2021) - Kong, Fanpeng; Wang, Xiaoxiu; Bai, Jundong; Li, Xiao; Yang, Chao; Li, Ying; Xu, Kehau; Tang, Bo
Abstract : A novel "double-locked" probe, DCO-H2 S-V, was prepared for detecting hydrogen sulfide in a highly viscous system and successfully used for detecting the changes of viscosity and H2 S in PC-12 cells. Abstract : A novel "double-locked" probe, DCO-H2 S-V, was prepared for detecting hydrogen sulfide in a highly viscous system. Experiments demonstrated that only when H2 S and a high viscosity environment coexist in a cell, can the probe be activated effectively and emit fluorescence. This has been successfully used for detecting the changes in viscosity and H2 S in a Parkinson's disease model, PC-12 cells treated with glutamate.